The Role of Purchasing Decisions in Mediating the Influence of Personal Selling, Price and Product Quality on Customer Satisfaction Using MICE Services - C. Catur Widayati; Fadhila Dhia Malihah; Purnamawati Hellen Widjaja; Yenita Yenita (Dinasti International Journal of Digital Business Management, 2023)
This study aims to analyze the effect of Personal Selling Services, Price, and Product Quality on customer satisfaction using MICE services. The object of this research is all customers of PT ABC. The population in this study is PT ABC customers in Jabodetabek, and the respondents' plan will be determined by the number of samples based on the Hair formula. Sampling will be carried out by purposive sampling method, which is a sample selected based on its characteristics. The analysis technique uses Smart PLS (Partial Least Square) 3.0 analysis. Quantitative analysis methods with SEM analysis tools and Smart PLS 3.3 tools. The results of this study show that Personal Selling has a positive and significant effect on Purchasing Decisions, but price shows a significant negative effect on Purchasing Decisions , besides that Product Quality shows a positive and significant effect on Purchasing Decisions. Therefore, considering the existing market share, companies should improve purchasing decisions by paying attention to service quality and product quality through the application of attractive prices. The Technology Readiness Level of this study is Level 3. Analytic and experimental critical functions and/or proofs of concept characteristics. Active research and development begins, this includes analytical studies and empirical studies to physically validate the analytical predictions of separate elements of the technology.